Does Islamic bank financing promote economic growth? Evidence from Indonesia - Ratna Mutia; Raja Masbar; M. Shabri Abd. Majid; Bismi Khalidin (Universitas Serambi Mekkah, 2024)
Over the past decade, Islamic banking has become an important sector in shaping the economy of Muslim-majority countries. This study aims to analyze the impact of Islamic banking on Indonesia's economic growth. This study employs quantitative methods, using Johansen cointegration testing and cointegrating regression. Quarterly data for the years 2010-2022 are used in this investigation. The results show that, in the long run, the variables of Islamic banking financing and economic growth are cointegrated. Furthermore, the causality test results show that Islamic bank financing contributes positively to economic growth in the short run, while in the long run, it contributes negatively. Despite the low contribution of Islamic banks to the economy, Islamic bank financing still has a vital role in the Indonesian economy.